Foundationalism, Coherentism and Naturalism: An Epistemological Survey - Ogaba, Isenyo Solomon (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
This work attempts a critical survey of Foundationalism, Coherentism and Naturalism as theories of justification for truth. In this work, I considered these three kinds of theories, the three different approaches to epistemology in general and their justification in particular. In making an exposition of foundationalism, I have made a distinction between foundationalism as a general epistemological approach and foundationalism as a specific approach to the theory of justification. Then, after describing the Regress Argument in defense of foundational beliefs, I made an exposition of Bonjour’s argument against foundationalism in terms of epistemic ascent argument. This argument demonstrates how any principle of justification can be challenged on the ground that a principle of justification itself may require justification. Employing Kornblith’s (1985) refutation of the Arguments-on-Paper Thesis, I find that coherentism and foundationalism have a commonly mistaken presupposition. The mistaken presupposition is that a justified belief is a belief identifiable with a good reason (argument) or based on such good reason which can be noted down on a piece of paper. Two important conclusions follow from my discussion on Arguments-on-Paper Thesis. One, coherentism and foundationalism can be put together on common ground. Two, insofar as the common ground is invalid, neither justification nor knowledge must have an explicit formal ground. In other words, through reason or good reason does matter for knowledge, reason need not be so formal that it can be noted down on a piece of paper.